Ethical challenges of using remote monitoring technologies for clinical research: a case study of the role of local research ethics committees in the RADAR-AD study - Muurling, Marijn; Pasmooij, Anna M. G.; Koychev, Ivan; Roik, Dora; Frölich, Lutz; Schwertner, Emilia; Religa, Dorota; Abdelnour, Carla; Boada, Mercè; Almici, Monica; Galluzzi, Samantha; Cardoso, Sandra; et al. (PLOS ONE, 2023)
Introduction Clinical research with remote monitoring technologies (RMTs) has multiple advantages over standard paper-pencil tests, but also raises several ethical concerns. While several studies have addressed the issue of governance of big data in clinical research from the legal or ethical perspectives, the viewpoint of local research ethics committee (REC) members is underrepresented in the current literature. The aim of this study is therefore to find which specific ethical challenges are raised by RECs in the context of a large European study on remote monitoring in all syndromic stages of Alzheimer’s disease, and what gaps remain. Methods Documents describing the REC review process at 10 sites in 9 European countries from the project Remote Assessment of Disease and Relapse-Alzheimer’s Disease (RADAR-AD) were collected and translated. Main themes emerging in the documents were identified using a qualitative analysis approach. Results Four main themes emerged after analysis: data management, participant’s wellbeing, methodological issues, and the issue of defining the regulatory category of RMTs. Review processes differed across sites: process duration varied from 71 to 423 days, some RECs did not raise any issues, whereas others raised up to 35 concerns, and the approval of a data protection officer was needed in half of the sites. Discussion The differences in the ethics review process of the same study protocol across different local settings suggest that a multi-site study would benefit from a harmonization in research ethics governance processes. More specifically, some best practices could be included in ethical reviews across institutional and national contexts, such as the opinion of an institutional data protection officer, patient advisory board reviews of the protocol and plans for how ethical reflection is embedded within the study.
Veröffentlicht: 7. Juli 2023
Gesehen am 31.08.2023